2018
DOI: 10.1186/s12864-018-4523-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scan for commons SNPs affecting bovine leukemia virus infection level in dairy cattle

Abstract: BackgroundBovine leukemia virus (BLV) infection is omnipresent in dairy herds causing direct economic losses due to trade restrictions and lymphosarcoma-related deaths. Milk production drops and increase in the culling rate are also relevant and usually neglected. The BLV provirus persists throughout a lifetime and an inter-individual variation is observed in the level of infection (LI) in vivo. High LI is strongly correlated with disease progression and BLV transmission among herd mates. In a context of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 117 publications
0
19
0
4
Order By: Relevance
“…Therefore, it is possible that the polymorphisms at the peptide-binding cleft in MHC class II molecules, responsible for the affinity of the bound peptides, influence the magnitude and extent of the elicited adaptive immune response and therefore the level of the proviral load. A genome-wide scan for single-nucleotide polymorphisms influencing the level of the proviral load in 800 BLV-infected cattle showed that all 24 significant associations were mapped to bovine chromosome 23, delimiting a region within the MHC [50]. Another conceivable mechanism underlying the control of the proviral load could be the action of other polymorphic genes within the MHC, acting independently or in linkage disequilibrium with BoLA-DRB3.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the polymorphisms at the peptide-binding cleft in MHC class II molecules, responsible for the affinity of the bound peptides, influence the magnitude and extent of the elicited adaptive immune response and therefore the level of the proviral load. A genome-wide scan for single-nucleotide polymorphisms influencing the level of the proviral load in 800 BLV-infected cattle showed that all 24 significant associations were mapped to bovine chromosome 23, delimiting a region within the MHC [50]. Another conceivable mechanism underlying the control of the proviral load could be the action of other polymorphic genes within the MHC, acting independently or in linkage disequilibrium with BoLA-DRB3.…”
Section: Discussionmentioning
confidence: 99%
“…The single nucleotide polymorphism (SNP) is the one nucleotide variation in the DNA sequence which will produce many polymorphisms in the genome of animals. It involves the transformation or transversion of a single nucleotide, which occurs in the sequence of the encoded protein or in the sequence of introns and intergenic regions (Dang et al, 2014). The SNP which happens in the CDS region will change and affect the protein if the mutation is the missense type.…”
Section: Introductionmentioning
confidence: 99%
“…Устойчивость к лейкозу связана с большим количеством генетических маркеров, многие из которых специфичны для отдельных пород КРС (Юдин и др., 2018б). В частности, недавно с помощью полногеномного анализа ассоциаций (GWAS) было идентифицировано несколько однонуклеотидных полиморфных маркеров (ОНП), связанных с чувствительностью КРС к инфекции ВЛКРС (Abdalla et al, 2016;Brym et al, 2016;Carignano et al, 2018). Но все эти исследования были выполнены на КРС голштинской породы и их гибридах.…”
Section: Introductionunclassified
“…Целью исследования была проверка ассоциации ОНП rs110861313 в межгенном участке хромосомы 23 с лейкозом у крупного рогатого скота черно-пестрой породы. Ранее по результатам полногеномного анализа этот ОНП был ассоциирован с провирусной нагрузкой ВЛКРС и количеством лейкоцитов в крови у голштинов и гибридов голштинов с джерси в Аргентине (Carignano et al, 2018).…”
Section: Introductionunclassified